A Soybean Deletion Mutant That Moderates the Repression of Flowering by Cool Temperatures - Zhang, Jingyu; Xu, Meilan; Dwiyanti, Maria Stefanie; Watanabe, Satoshi; Yamada, Tetsuya; Hase, Yoshihiro; Kanazawa, Akira; Sayama, Takashi; Ishimoto, Masao; Liu, Baohui; Abe, Jun (Frontiers in Plant Science, 2020)
Ambient growing temperature and photoperiod are major environmental stimuli that summer annual crops use to adjust their reproductive phenology so as to maximize yield. Variation in flowering time among soybean (Glycine max) cultivars results mainly from allelic diversity at loci that control photoperiod sensitivity and FLOWERING LOCUS T (FT) orthologs. However, variation in the thermal regulation of flowering and its underlying mechanisms are poorly understood. In this study, we identified a novel mutant that confers altered thermal regulation of flowering in response to cool ambient temperatures. Mapping analysis with simple sequence repeat markers located the mutation in the upper part of chromosome 19, where no QTL for flowering has been previously reported. Fine-mapping and re-sequencing revealed that the mutation was caused by deletion of a 214-kbp genomic region that contains 11 annotated genes, including COL2b, a soybean ortholog of Arabidopsis CONSTANS. Comparison of flowering times under different photo-thermal conditions revealed that early flowering in the mutant lines was most distinct under cool ambient temperatures. The expression of two FT orthologs, FT2a and FT5a, was dramatically downregulated by cool temperature, but the magnitude of the downregulation was lower in the mutant lines. Cool temperatures upregulated COL2b expression or delayed peak expression, particularly at the fourth trifoliate-leaf stage. Intriguingly, they also upregulated E1, a soybean-specific repressor of FT orthologs. Our results suggest that the ef1 mutation is involved in thermal regulation of flowering in response to cool ambient temperature, and the lack of COL2b in the mutant likely alleviates the repression of flowering by cool temperature. The ef1 mutant can be used as a novel gene resource in breeding soybean cultivars adapted to cool climate and in research to improve our understanding of thermal regulation of flowering in soybean.